P20 Delineating The Contribution Of Formylated Peptides And Formyl Peptide Receptor 1 To The Pathogenesis Of Acute Lung Injury. (10th November 2014) - Dorward, DA; Lucas, CD; Doherty, MK; Chapman, GB; Scholefield, E; Conway-Morris, A; Kipari, T; Robb, CT; Felton, JM; Whitfield, PD; Haslett, C; Dhaliwal, K; et al.
Abstract : Background: Acute respiratory distress syndrome (ARDS) remains an often fatal condition without effective pharmacological therapies. Characteristically, a neutrophil-dominant disorder, it is associated with a dysregulated inflammatory response and tissue injury. Neutrophil migration into inflammatory sites is controlled by a variety of factors; in sterile tissue injury mitochondrial formylated peptides are released following necrotic cell death and bind to formyl peptide receptor 1 (FPR1) on neutrophils to induce migration and activation. Hypothesis: That mitochondrial formylated peptides are elevated in ARDS and drive FPR1-mediated neutrophil recruitment. Inhibition of FPR1 in sterile lung injury would therefore attenuate the inflammatory response through multiple FPR1-mediated effects. Methods: Mitochondrial DNA and formylated peptides were quantified in plasma of ARDS patients and healthy controls by qPCR, western blot and LC-MS/MS. Healthy volunteer neutrophils were stimulated with mitochondrial formylated peptides and chemotaxis assays and flow cytometry used to assess neutrophil function. Intracellular signalling was assessed by western blotting. Mouse models of infective (E. coli) and sterile (hydrochloric acid) acute lung injury were used. Results: Free mitochondrial DNA and formylated peptides were elevated in ARDS patients. Mitochondrial formylated peptides induced FPR1-dependent neutrophil chemotaxis through PI3K- and MAPK-mediated control of the β2 -integrin heterodimer Mac1. In sterile acid-induced injury FPR1 inhibition resulted in reduced neutrophil migration, pulmonary haemorrhage, protein leak and pro-inflammatory cytokine expression. Furthermore, acid-induced reduction in alveolar macrophage number was inhibited while interstitial macrophages displayed an alternatively activated phenotype. FPR1 was also found to be expressed on mouse type 1 alveolar epithelial cells suggesting further possible mechanisms through which FPR1-mediated alveolar leak occurs. Importantly, delivery of FPR1 antagonists 12 h after injury also reduced acute lung inflammation demonstrating potential therapeutic relevance. In non-sterile E. coli-mediated lung injury partial antagonism of FPR1 resulted in reduced alveolar neutrophil numbers and attenuated vascular leak without altering bacterial clearance. Conclusions: Mitochondrial formylated peptides and FPR1 play an important role in the pathogenesis of sterile acute lung injury. This appears to be predominantly through neutrophil-dependent means but their role in macrophage and epithelial cell function could also be important. FPR1 antagonism may therefore represent a multi-cellular therapeutic target in the treatment of ARDS.